STRATEGI INDUSTRIALISASI PADA EKONOMI MAKRO YANG ADA DI KOTA SURABAYA - Risky Agustin Widyanti; Muhammad Yasin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study explores the role of industrialization strategies in supporting macroeconomic growth in Surabaya City. As an economic hub in eastern Indonesia, Surabaya has demonstrated solid economic performance, with a growth rate reaching 5.76 percent in 2024. The study highlights the contribution of the manufacturing sector to the Gross Regional Domestic Product (GRDP), accounting for 19.07 percent, and the dominant role of the wholesale and retail trade sector, contributing 27.75 percent. A descriptive quantitative approach was used, utilizing secondary data from official institutions such as the Central Statistics Agency. The findings indicate that industrialization plays a vital role in strengthening the city’s economic structure through value creation, employment generation, and regional competitiveness. The study recommends a more integrated industrialization strategy aligned with innovation policies, human capital development, and multi-sector collaboration. Such an approach is essential to reinforce Surabaya’s inclusive and sustainable macroeconomic foundation. Keywords: industrialization; macroeconomy; Surabaya; GRDP; economic growth